1982
DOI: 10.1111/j.1600-0722.1982.tb01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of gold alloys and titanium in artificial saliva

Abstract: – Two types of gold alloys and one type of pure titanium have been submitted to corrosion in artificial saliva for periods of up to about 2 months. The release of copper, gold or silver from the golod alloys as well as titanium from the titanium matrix was measured with nuclear tracer technique. The physical/chemical state of the corrosion products of gold alloys referring to the ionic state or presence in particulate form has been examined retaining the particulate matter on a glass filter. Copper wad observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
0
16
0
3
Order By: Relevance
“…Compared with other non-noble dental alloys, pure Ti reportedly had better corrosion properties and biocompatibility 14,24,30) . In this study, RTI alloy showed moderate ion release in all the immersion solutionswhich could be attributed to a passive oxide film covering the titanium alloy surface.…”
Section: Corrosion Behavior Of Timentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other non-noble dental alloys, pure Ti reportedly had better corrosion properties and biocompatibility 14,24,30) . In this study, RTI alloy showed moderate ion release in all the immersion solutionswhich could be attributed to a passive oxide film covering the titanium alloy surface.…”
Section: Corrosion Behavior Of Timentioning
confidence: 99%
“…Studies have shown that dental alloys which contained less than 50% of noble metals exhibited tarnish and corrosion 2,13) . Therefore, biological risks can be kept to a minimum with the use of high-noble and noble alloys because ion release from these alloys is lower 1,2,10,[13][14][15] . Nonetheless, there were conflicting reports on ion release behavior from noble alloys in low pH conditions, which could be attributed to differences of the environment surrounding the tested alloys 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and titanium alloys have excellent chemical stability and exhibit corrosion resistance in various test solutions such as artificial saliva, Ringer' s solution, and physiological saline solution [14][15][16] . However, such corrosion resistance was lost in solutions which contain fluoride with varying pH values 17) .…”
Section: Discussionmentioning
confidence: 99%
“…These near-equiatomic NiTi alloys have many excellent properties such as adequate springback, low stiffness, superelasticity, and shape memory which are essential for orthodontic purposes [10][11][12][13] . NiTi alloys also have excellent biocompatibility with living tissue and corrosion resistance in various simulated body fluids and NaCl solutions [14][15][16] . These properties originate from the spontaneously formed oxide passivation layer.…”
Section: Introductionmentioning
confidence: 99%
“…This corrosion resistance was confirmed in various simulated body fluids and NaCl solutions. [7][8][9] However, NiTi alloys showed an increased corrosion rate in solutions containing chlorine ions such as HCl and FeCl 3 . 2 Additionally, some NiTi wires have been reported to degrade and fracture in the oral cavity after setting.…”
Section: Introductionmentioning
confidence: 99%